IMPLEMENTATION OF AN AGROFORESTRY SYSTEM AS A REFORESTATION INSTRUMENT IN THE CAATINGA BIOME - Rodrigues Maia, Felipe (Journal of Interdisciplinary Debates, 2023)
The relevance of the agroforestry system not only for farmers, but also for the environment and the growth of their knowledge is the reason for this work, particularly because the agroforestry system has been established and is producing results in the Sertão da Caatinga region. The Caatinga is the dominant biome in the northeast region of Brazil, which has suffered over the years as a result of intensive commercial exploitation. This exploitation converted more than half of its land into desertified regions. The implementation of the agroforestry system was motivated by the desire to preserve the Caatinga and its ecosystem. The regional drought itself, the creation of cisterns to capture water, strategies for less drainage, and the production of food without pesticides can be counted among the challenges overcome, and non-deforestation, the benefits for the Caatinga biome, and the Production of healthy food for subsistence can be counted among the results achieved, all of them culminating in the dissemination with the same environmental characteristics. As a result, studies are being conducted in an effort to reduce the harmful effects of these behaviors. Based on this, the objective of this study is to evaluate the implementation of an Agroforestry System as a strategy for the recovery of degraded regions in an area considered to be in an accelerated phase of desertification in the hinterland biome.